Lipophagy pathways in yeast are controlled by their distinct modes of induction. Issue 8 (2nd June 2022) - Fairman, Garrett; Ouimet, Mireille
Abstract: Lipid droplet (LD) autophagy (lipophagy) is a recently discovered selective form of autophagy and is a pathway for LD catabolism. This ubiquitous process has been an ongoing area of research within the budding yeast, Saccharomyces cerevisiae . Yeast lipophagy phenotypically resembles microautophagy, although it has a distinct set of genetic requirements depending on the mode of induction. This review highlights the similarities and differences between different forms of yeast lipophagy and offers perspectives on how our knowledge of lipophagy in yeast may guide our understanding of this process within mammalian cells to ultimately inform future applications of lipophagy. Abstract : Lipophagy in Saccharomyces cerevisiae phenotypically resembles microautophagy and has different genetic requirements depending on the mode of induction. Herein, we highlight the differences between yeast lipophagy modes, and discuss how macroautophagy, the endosomal sorting complex required for transport (ESCRT) pathway, and partitioning of the vacuolar membrane into distinct microdomains are involved in this process. Take Away: Yeast lipophagy resembles microautophagy and requires vacuolar microdomains. There are different genetic requirements for lipophagy dependent on the induction method used. Contrasting role for the endosomal sorting complex in distinct lipophagy forms. Macroautophagy genes are indispensable for most yeast lipophagy forms. Yeast lipophagy may inform future studies into mammalian lipophagy.